Molecular insights into the normal operation, regulation, and multisystemic roles of K + -Cl − cotransporter 3 (KCC3) - Garneau, A. P.; Marcoux, A. A.; Frenette-Cotton, R.; Mac-Way, F.; Lavoie, J. L.; Isenring, P. (American Journal of Physiology: Cell Physiology, 2017)
Long before the molecular identity of the Na + -dependent K + -Cl − cotransporters was uncovered in the mid-nineties, a Na + -independent K + -Cl − cotransport system was also known to exist. It was initially observed in sheep and goat red blood cells where it was shown to be ouabain-insensitive and to increase in the presence of N-ethylmaleimide (NEM). After it was established between the early and mid-nineties, the expressed sequence tag (EST) databank was found to include a sequence that was highly homologous to those of the Na + -dependent K + -Cl − cotransporters. This sequence was eventually found to code for the Na + -independent K + -Cl − cotransport function that was described in red blood cells several years before. It was termed KCC1 and led to the discovery of three isoforms called KCC2, KCC3, and KCC4. Since then, it has become obvious that each one of these isoforms exhibits unique patterns of distribution and fulfills distinct physiological roles. Among them, KCC3 has been the subject of great attention in view of its important role in the nervous system and its association with a rare hereditary sensorimotor neuropathy (called Andermann syndrome) that affects many individuals in Quebec province (Canada). It was also found to play important roles in the cardiovascular system, the organ of Corti, and circulating blood cells. As will be seen in this review, however, there are still a number of uncertainties regarding the transport properties, structural organization, and regulation of KCC3. The same is true regarding the mechanisms by which KCC3 accomplishes its numerous functions in animal cells.